2005
DOI: 10.2174/1568009054064633
|View full text |Cite
|
Sign up to set email alerts
|

The Anti-Tumor Effect and Mechanisms of Action of Penta-Acetyl Geniposide

Abstract: Gardenia, the fruit of Gardenia jasminoides Ellis, has been widely used to treat liver and gall bladder disorders in Chinese medicine. It has been shown recently that geniposide, the main ingredient of Gardenia Fructus, exhibits the anti-tumor effect. In this review, we discuss the anti-tumor effect and possible mechanisms of a derivative from Gardenia Fructus, penta-acetyl geniposide ((Ac)5GP). It has been demonstrated that (Ac)5GP plays more potent roles than geniposide in chemoprevention. (Ac)5GP decreased … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 71 publications
0
13
0
Order By: Relevance
“…The fruits of Gardenia jasminoides (Rubiaceae) (Korean herbal name is Chi Za) have been used as a natural yellow colorant in foods and also in traditional medicine for the treatment of liver and bladder disorders and inflammatory disease. The major effective constituents of Gardenia fruits, iridoid glycosides, flavonoids, and carotenoids, are responsible for the biological activities such as hypoglycemic activity, anti-tumor effect, anti-angiogenic activity, antithrombotic effect, and anti-oxidant activity (Miura et al , 1996; Pham et al , 2000; Suzuki et al , 2001; Koo et al , 2004; Peng et al , 2005). In our previous research, cold drugs inhibited the activity of MAO (Hwang et al , 1999) and especially, the total methanolic extract of the fruit of G. jasminoides exhibited a significant inhibition on MAO activity (IC 50 value of MAO-A is 1.23 mg/ml; MAO-B is 1.34 mg/ml) (Hwang, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…The fruits of Gardenia jasminoides (Rubiaceae) (Korean herbal name is Chi Za) have been used as a natural yellow colorant in foods and also in traditional medicine for the treatment of liver and bladder disorders and inflammatory disease. The major effective constituents of Gardenia fruits, iridoid glycosides, flavonoids, and carotenoids, are responsible for the biological activities such as hypoglycemic activity, anti-tumor effect, anti-angiogenic activity, antithrombotic effect, and anti-oxidant activity (Miura et al , 1996; Pham et al , 2000; Suzuki et al , 2001; Koo et al , 2004; Peng et al , 2005). In our previous research, cold drugs inhibited the activity of MAO (Hwang et al , 1999) and especially, the total methanolic extract of the fruit of G. jasminoides exhibited a significant inhibition on MAO activity (IC 50 value of MAO-A is 1.23 mg/ml; MAO-B is 1.34 mg/ml) (Hwang, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…1] is an herbal derivative prepared from Gardenia geniposide. It has been suggested that (Ac) 5 GP plays more potent roles than geniposide in chemoprevention (Peng et al, 2005a). In addition, (Ac) 5 GP possesses the antitumor effect on apoptosis and growth arrest (Wang et al, 1993;Chang et al, 2002Chang et al, , 2004.…”
mentioning
confidence: 99%
“…The bioactivities of geniposide have been identified in numerous studies, including anti-oxidant (Yin et al ., 2010), antitumor (Peng et al ., 2005), and anti-inflammation bioactivities, however, the most important aspect of geniposide concerns its anti-oxidative capacity. Geniposide protected rat hippocampal slice cultures against oxygen and glucose deprivation-induced neuronal cell death (Lee et al ., 2006).…”
Section: Discussionmentioning
confidence: 99%